2001
DOI: 10.4049/jimmunol.167.4.2240
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Pseudomonas aeruginosa in the Bloodstream with Bispecific Monoclonal Antibodies

Abstract: We examined the ability of a bispecific mAb reagent, consisting of a mAb specific for the primate erythrocyte complement receptor cross-linked with an anti-bacterial mAb, to target bacteria in the bloodstream in an acute infusion model in monkeys. In vitro studies demonstrated a variable level of complement-mediated binding (immune adherence) of Pseudomonas aeruginosa (strain PAO1) to primate E in serum. In vivo experiments in animals depleted of complement revealed that binding of bacteria to E was <1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…The Taylor group, in series of elegant papers, reports the use of several different bi-specific fusion proteins (BiFPs) that enhanced phagocytosis by macrophage of various pathogens, including: E. coli (Kuhn et al, 1998), P. aeruginosa (Lindorfer et al, 2001), and S. aureus (Gyimesi et al, 2004). In all cases, BiFPs consisted of (1) a molecule that recognizes a surface marker on the pathogen that was chemically coupled with (2) a Mab that is specific to the complement receptor 1 (CR1) present on primate erythrocytes.…”
Section: Enhancing Phagocytosismentioning
confidence: 99%
“…The Taylor group, in series of elegant papers, reports the use of several different bi-specific fusion proteins (BiFPs) that enhanced phagocytosis by macrophage of various pathogens, including: E. coli (Kuhn et al, 1998), P. aeruginosa (Lindorfer et al, 2001), and S. aureus (Gyimesi et al, 2004). In all cases, BiFPs consisted of (1) a molecule that recognizes a surface marker on the pathogen that was chemically coupled with (2) a Mab that is specific to the complement receptor 1 (CR1) present on primate erythrocytes.…”
Section: Enhancing Phagocytosismentioning
confidence: 99%
“…Gel filtration analyses (data not shown) revealed that mAbs prepared by this procedure are Ͼ98% monomeric after purification. mAb 7B7 (IgG2a), specific for bacteriophage ⌽X174, has been previously described (36), and was covalently crosslinked to mAb 7G6 using published procedures (37,38). mAbs were labeled with 125 I using Iodogen (39), with Alexa fluorophore (Al) dyes (Al488, Al594, or Al633; Molecular Probes, Eugene, OR) following the manufacturer's directions, or were conjugated with NHS LC biotin (bt; Pierce, Rockford, IL) (40).…”
mentioning
confidence: 99%
“…We have found that by constructing bispecific mAb complexes (HP), it is possible to use the anti-CR1 mAb as a surrogate for C3b to facilitate binding of particulate pathogens to E, independent of complement opsonization [7,9,17]. The purpose of the present experiments was to determine whether a clinically relevant strain of S. aureus, bound to human E via HP, could be recognized, removed from E, internalized and killed by acceptor macrophages.…”
Section: Immune Adherence and Hpmentioning
confidence: 98%
“…We prepared HP by coupling mAb 072 with anti-CR1 mAb 9H3 (IgG1 isotype) using previously published methods [9,12]. Biotinylated mAb 012, which is specific for a different site on the T5 isolate, was used for identifying bacteria internalized by macrophages.…”
Section: Mabs Hpmentioning
confidence: 99%
See 1 more Smart Citation